A case of autoimmune progesterone dermatitis - Ana G. Lopes; Catarina Cerqueira; Carlos Nogueira; Joana Gomes; Celeste Brito (Sociedade Portuguesa de Dermatologia e Venereologia, 2024)
A 41-year-old female patient presents to the dermatology department with a 3-year history of a monthly relapsing pruritic eruption. These lesions appear 5-7 days before the onset of menses and resolve 3-4 days after menstruation. During her two previous pregnancies, she had no symptoms. She had been previously treated with antihistamines and oral corticosteroids with only temporary relief. On examination, during the luteal phase, the patient presented multiple maculopapular pruritic wheals distributed throughout the body. Several laboratory studies were performed and were all normal or negative, including auto-antibodies tests and hormonal analysis. Patch tests with the standard series of the Portuguese Contact Dermatitis Group, corticosteroid series, and metal series revealed positive reactions to nickel sulfate (++) and palladium chloride (+) at 72 h. An intradermal test with medroxyprogesterone at concentrations of 0.1 and 10 mg/mL was performed on the 7th day of the menstrual cycle. The test was positive 2 h after the injection and persisted for 24 h. The diagnosis of autoimmune progesterone dermatitis was made and the patient started tamoxifen 40 mg/day, with almost complete clinical clearing. Four months after, the dose was reduced, with no relapsing. Six months later, the patient remains free of symptoms.